Molecular analysis of microbial communities in nitrification and denitrification reactors treating high ammonia leachate - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT (My University, 2003)
Molecular analysis of microbial populations in two bench-scale nitrification and denitrification reactors fed with high ammonia landfill leachate was conducted in this study by using DGGE, cloning, and FISH techniques in addition to classical efficiency control parameters. Nitrification tank was operated with a computer-controlled alkalinity dosing system to supply the alkalinity intermittently as consumed on the basis of on-line pH monitoring. By keeping the pH at 7.0 with this system, 99% nitrification efficiency and rates of about 0.14-0.18 mgNH4+-N/mgVSSday were obtained. Meanwhile, as ammonia oxidizing bacteria Nitrosomonas and Nitrosococcus mobilis-like cells and as nitrite oxidizing bacteria Nitrobacter-related cells were intensively indicated. Moreover, some aerobic denitrifiers as Thauera species were also identified. After the termination of pH adjustment in the preceding anaerobic reactors, nitrification tank was loaded with more biodegradable COD as a result of reduced COD removal in anaerobic reactors. Microbial diversity was immediately affected from this alteration and heterotrophic carbonaceous bacteria and aerobic denitrifiers have dominated. To provide the former high efficiencies, retention time has increased from 24 to 48 h and a second pump dosing HCl was included to the automatic control system. Subsequent to these precautions, numbers of ammonia (Nso190) and nitrite oxidizing bacteria (NIT3) were comparatively increased. In denitrification system, about 98% denitrification efficiencies were obtained at 2000 mg/L NOx-N concentrations if sodium acetate was supplied as carbon source. Meanwhile, with 20 gVSS/l biomass concentration, denitrification rates of about 1.34 mgNOx-N/mgVSSday were obtained. All sludge samples have represented similar DGGE patterns and Paraccoccus-related species were identified as dominant denitrifying bacteria.
Keywords: DNA, Bacterial; Hydrogen-Ion Concentration; Refuse Disposal; Oxidation-Reduction; Bioreactors; Ammonia; Population Dynamics; Electrophoresis, Gel, Two-Dimensional; In Situ Hybridization, Fluorescence; Nitrogen; Soil Microbiology; Bacteria, Aerobic; Water Pollutants